Cautionary response strategy and impairment of post-conflict response selection underlie age-related differences in a location-based Stroop task - Pournaghdali, Ali; Eich, Teal S. (Frontiers in Psychology, 2025)
IntroductionResearch suggests that older adults have deficits in selective attention, a cognitive process often queried through the Stroop task. To tease apart whether this is due to failures to inhibit distracting information or to upregulate attention towards target information, younger and older adults completed a task called the Shape Stroop.MethodsIn this task, participants had to name the color of a shape that was occluded by another shape. Critically, congruent or incongruent Stroop words were placed in either the target shape, the occluding (distractor) shape or in the background. We first modeled performance as a function of age-group, Stroop word congruency, and location.ResultsThe results indicate that older adults were more accurate but slower than younger adults to choose the correct shape color. For both younger and older adults, incongruent words induced slower reaction times when words were in the target location, indicating age-invariance in the Stroop effect. To further probe how early and/or late attentional processes contribute to performance and to interrogate the decision strategies adopted across different conditions, we also fit the dual-stage two-phase model of selective attention to our data.DiscussionOur results indicate that older adults tend to be more cautious and require more information before choosing a stimulus to attend to or making a decision. Although older adults’ ability to inhibit irrelevant information seems intact, they show signs of slower information processing in the later stages of attentional processing.